Topics and opinions - A. F. Scott; Bernoth, Eva-Maria.; ScienceDirect (Online service) (San Diego ; London : Academic Press, 1997)
Furunculosis: Multidisciplinary Fish Disease Research presents a fascinating insight into the opinions and the controversies which have led to current knowledge of this disease. It is the first book to cover one single fish disease by presenting not just the reviews, but also critical examination of the progress made by various disciplines. The multidisciplinary approach of the book makes it a valuable guide for veterinarians, fisheries biologists, and fish farm managers, as well as an excellent instructional text for students. The volume explores current research strategies and projects what developments can be expected in each field. Key Features * Considers the whole disease and not just the pathogen, Aeromonas salmonicida * Analyzes the state of modern knowledge on the disease * Suggests topics for future research and uses furunculosis as a model for other diseases * Highlights and summarizes each section's themes and concepts * Presents a unique compendium of research information for all professionals working on furunculosis.
P. Smith, Preface. -- E.-M. Bernoth, Furunculosis: The History of the Disease and of Disease Research. -- P. Smith, Section I: -- P. Smith, Introduction: Towards An Epizootiology of Furunculosis. -- P. Smith, The Epizootiology of Furunculosis: The Present State of Our Ignorance. -- M. Hiney, P. Smith, and E.-M. Bernoth, Covert Aeromonas salmonicida Infections. -- E.-M. Bernoth, Diagnosis of Furunculosis: The Tools. -- O. Enger, Survival and Inactivation of Aeromonas salmonicida Outside the Host--A Most Superficial Way of Life. -- A.D. Pickering, Husbandry and Stress. -- P. Smith, Furunculosis Research as Seen from a Fish Farm. -- G. Olivier, Section II: -- G. Olivier, Introduction: Getting to Know Your Enemy. -- W.W. Kay and T. Trust, The Surface of Aeromonas salmonicida: What Does it Look Like and What Does it Do? -- A.E. Ellis, The Extracellular Toxins of Aeromonas salmonicida Subspecies salmonicida. -- C.J. Secombes and G. Olivier, Host-Pathogen Interactions in Salmonids. -- L.M. Vaughan, Aeromonas salmonicida Subspecies salmonicida--A Molecular Genetic Perspective. -- P J. Midtlyingand A.E. Ellis, Section III: Introduction: Raising Resistance against Furuncolosis. -- G. Olivier, Effect of Nutrition on Furunculosis. -- D.P. Anderson, G. Jeney, G.L. Rumsey, and A.K. Siwicki, Adjuvants and Immunostimulants for Potentiating Protection Against Furunculosisin Fish. -- A.E. Ellis, Furunculosis Protective Antigens and Mechanisms. -- P.J. Midtlyng, Vaccination against Furunculosis. -- T. Gjedrem, Breeding to Raise Resistance. -- A.E. Ellis, Section IV: -- A.E. Ellis, Introduction: Treatment. -- T.S. Hastings, Chemotherapy of Furunculosis. -- T. Aoki, Resistance Plasmids and the Risk of Transfer. -- P. Smith, Conclusions. -- Subject Index.
Includes bibliographical references (p. 446-512) and index.
Keywords: Civilization